Performance after timely cochlear implantation in prelingually deaf children with cerebral palsy - Byun, Hayoung; Moon, Il Joon; Kim, Eun Yeon; Park, Junoh; Kwon, See Youn; Han, Hyo Dam; Chung, Won-Ho; Cho, Yang-Sun; Hong, Sung Hwa (International journal of pediatric otorhinolaryngology, 2013)
To investigate auditory perception, speech production, and language ability of prelingually deaf toddlers with cerebral palsy (CP) who were implanted within a sensitive period and who received proper speech therapy. Comparison of their outcomes with age- and sex-matched CI recipients without additional disabilities was also performed. We retrospectively reviewed a cohort of pediatric CI in Samsung Medical Center. Eight CP subjects who received CI before 3 years of age and age–sex matched control recipients who had no additional disabilities except idiopathic sensorineural hearing loss (SNHL) were included for the analysis. Preoperative evaluation included the Categories of Auditory Performance (CAP) score, Korean Version of the Ling's Stage (K-Ling), Sequenced Language Scale for Infants (SELSI), Bailey Scales of Infant Development II assessment, Social Maturity Scale test, and grading of CP severity using severity level and Gross Motor Function Classification System for CP (GMFCS). To measure the outcome, the CAP scores, K-Ling, and SELSI were performed at 3, 6, 12, and 24 months after implantation. Four CP children with outstanding performances showed comparable achievement with matched control recipients. These patients had less severe motor disabilities (mild–moderate severity, GMFCS level 1–3), better social quotient, and better cognitive abilities. Although the others showed poor language abilities and hardly produced meaningful speech, their CAP scores reached 1 or 2 in 24 months after implantation. Deaf children with CP could have various ranges of benefits up to the levels of normal peers whose only disability was hearing loss, when CI was performed within a critical period. Especially, children with mild or moderate CP had a favorable outcome after CI, equivalent to that of normal peers.